Headache prevalence and its functional impact among HIV-infected adults in rural Rakai District, Uganda - Sohail, Sachal (J Neurovirol, 2019)
Headache is common, but its prevalence and impact in sub-Saharan Africa and especially in HIV+ individuals is relatively unknown. We sought to determine the prevalence and functional impact of headache among HIV-infected (HIV+) adults in a cross-sectional observational cohort study in rural Rakai District, Uganda. Participants completed a sociodemographic survey, depression screen, functional status assessments, and answered the headache screening question, “Do you get headaches?” Participants responding affirmatively were assessed with the ID Migraine tool for diagnosis of migraine and Headache Impact Test-6 to determine functional impact of headache. Characteristics of participants with and without headaches and with and without functional impairment were compared using t-tests for continuous variables, chi-square tests for categorical variables, and multivariate logistic regression. Of 333 participants, 51% were males, mean age was 37 (SD 9) years, 94% were on antiretroviral therapy (ART) and mean CD4 count was 403 (SD 198) cells/µL. Headache prevalence was 28%. Among those reporting headache, 19% met criteria for migraine, 55% reported functional impairment, and 37% reported substantial or severe impact of headache. In multivariate analyses, female sex (odds ratio (OR) 2.58) and depression (OR 2.49) were associated with increased odds while ART (OR 0.33) decreased odds of headache. Participants with substantial/severe functional impact were more likely to meet criteria for depression (32% vs 9%). In conclusion, headache prevalence in HIV+ rural Ugandans was lower than global averages but still affected more than one-quarter of participants and was associated with significant functional impairment.